2019
DOI: 10.3389/fmicb.2019.00611
|View full text |Cite|
|
Sign up to set email alerts
|

Signal Disruption Leads to Changes in Bacterial Community Population

Abstract: The disruption of bacterial signaling (quorum quenching) has been proven to be an innovative approach to influence the behavior of bacteria. In particular, lactonase enzymes that are capable of hydrolyzing the N- acyl homoserine lactone (AHL) molecules used by numerous bacteria, were reported to inhibit biofilm formation, including those of freshwater microbial communities. However, insights and tools are currently lacking to characterize, understand and explain the effects of signal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 78 publications
6
27
0
Order By: Relevance
“…Yet, reports demonstrate the ability of QQ enzymes, and particularly lactonases, to have a biological effect beyond isolated gram-negative bacterial stains including the inhibition of biofouling [57, 58]. Specifically, the ability of heterologously expressed lactonases to decrease fouling in membrane bioreactors was repeatedly demonstrated [41, 56–58]. In this study, we demonstrated the ability of a purified, extremely stable lactonase to inhibit biocorrosion over a period of 8 weeks in a complex aquatic microbial community.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, reports demonstrate the ability of QQ enzymes, and particularly lactonases, to have a biological effect beyond isolated gram-negative bacterial stains including the inhibition of biofouling [57, 58]. Specifically, the ability of heterologously expressed lactonases to decrease fouling in membrane bioreactors was repeatedly demonstrated [41, 56–58]. In this study, we demonstrated the ability of a purified, extremely stable lactonase to inhibit biocorrosion over a period of 8 weeks in a complex aquatic microbial community.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it has been shown that lactonase has the modulating effect on the composition of biofilm and planktonic soil microorganisms. The most significant changes were observed for Stenotrophomonas and Pseudomonas (increase), as well as Clostridium cluster XIVa (decrease) (Schwab et al, 2019). Although the experiment was conducted against soil bacteria, these observations indicate the possibility of quantitative changes in microorganisms exposed to factors limiting the QS activity.…”
Section: The First Objection – the Selectivity Of Quorum Quenching Sumentioning
confidence: 99%
“…These enzymes therefore constitute promising candidates to control bacterial virulence and biofilms (Whiteley et al, 2017). Using lactonases may be advantageous to control virulence and biofilm formation over other strategies because these enzymes are not biocidal, and were previously shown to not need contact with bacteria for their activity (Oh et al, 2012;Schwab et al, 2019). Therefore, the risk of resistance (Defoirdt et al, 2010) may be lessened compared to antibiotics (Gerdt and Blackwell, 2014;García-Contreras et al, 2016).…”
Section: Introductionmentioning
confidence: 99%